2020
DOI: 10.3389/fmars.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Operational Modeling Capacity in European Seas—An EuroGOOS Perspective and Recommendations for Improvement

Abstract: www.uliege.be Croatia Ruder Boskovic Institute (IRB) www.irb.hr/eng Cyprus Joint Research and Development Center-ORION www.orioncyprus.org Denmark Joint GeoMETOC Support Center www.mgeometoc-coe.org " Danish Meteorological Institute (DMI) http://ocean.dmi.dk/english/index.php Finland Finnish Meteorological Institute (FMI) en.ilmatieteenlaitos.fi France SHOM www.shom.fr " Meteo-France www.meteofrance.com Germany Federal Maritime and Hydrographic Agency (BSH) www.bsh.de " Helmholtz-Zentrum Geesthacht (HZG) www.h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…This multi-model assessment focused on the Storm Gloria has allowed identifying the strengths and limitations of the present operational capability in the Spanish Mediterranean coast to forecast an extreme coastal event. Apart from the classical recipes needed for the evolution of operational ocean model systems (i.e., increasing resolution to simulate finer scales, atmospheric forcing improving, introducing more-advanced data assimilation methods with inclusion of coastal and on-shelf observations), which are usually taken into account in service evolution roadmaps [see Le Traon et al (2019) and Capet et al (2020) for the CMEMS evolution guidelines and the EuroGOOS perspectives for improvement of operational ocean modeling capacity in Europe], the present study has pointed out some shortcomings in the current existing services that should be considered to make of them operational tools adequate to forecast extreme coastal events such as the Storm Gloria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multi-model assessment focused on the Storm Gloria has allowed identifying the strengths and limitations of the present operational capability in the Spanish Mediterranean coast to forecast an extreme coastal event. Apart from the classical recipes needed for the evolution of operational ocean model systems (i.e., increasing resolution to simulate finer scales, atmospheric forcing improving, introducing more-advanced data assimilation methods with inclusion of coastal and on-shelf observations), which are usually taken into account in service evolution roadmaps [see Le Traon et al (2019) and Capet et al (2020) for the CMEMS evolution guidelines and the EuroGOOS perspectives for improvement of operational ocean modeling capacity in Europe], the present study has pointed out some shortcomings in the current existing services that should be considered to make of them operational tools adequate to forecast extreme coastal events such as the Storm Gloria.…”
Section: Discussionmentioning
confidence: 99%
“…The sustained availability of CMEMS global and regional scale core products has fostered the development of "downstream" services devoted to coastal monitoring and forecasting. Capet et al (2020) in their review of the current European capacity on operational marine and coastal modeling systems, map 49 organizations around Europe delivering 104 operational model systems simulating mostly hydrodynamics, biogeochemistry and sea waves at regional and coastal scales, in some cases on overlapping areas. In this context, with different model products available in some specific coastal areas, the opportunity and the need arise to compare model solutions, thus identifying the strengths and shortcomings of each model system.…”
Section: Introductionmentioning
confidence: 99%
“…CMEMS operational ocean systems are routinely used as forcing for more local, downscaled ocean operational systems. An overview of the current European capacity in terms of operational modeling of marine and coastal systems was recently presented in Capet et al (2020) and indicated that about half of the reported regional / local ocean modeling systems rely on CMEMS models for open boundary conditions. A review of storm surge modeling for Europe is provided in Umgiesser et al (2020), with several systems also part of CMEMS or using CMEMS as boundary conditions.…”
Section: Downscaling Copernicus Forecastsmentioning
confidence: 99%
“…The latest review of the current European capacity in terms of operational marine and coastal modeling systems [22] maps the organizations and the operational model systems at regional and coastal scales across Europe and points out the sustained availability of CMEMS global and regional scale core products as a positive driver to favor proliferation of "downstream" services devoted to coastal monitoring and forecasting. Likewise, this review highlights the availability of different operational ocean models, covering in some cases overlapped areas.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Matulka et al [24] inform that the approaches followed to include freshwater inputs in each operational forecast system, shown in Figure 1, vary from one model set-up to another, using: (1) data derived from daily observations taken in river flow stations (i.e., the MeteoGalicia MTG-ROMS set-up and the CMEMS IBI one, but this one using observations only for some of the major rivers), (2) daily freshwater discharges at river mouths produced by hydrological models (this is the case for IBI, especially for its five-days-ahead forecast run), (3) data derived from river discharge monthly climatology (a very common approach, fully or partially used in IBI, The MyCoast multi-model intercomparison exercise is further proof of the necessity to improve coastal freshwater signals in operational ocean models. This need, already identified within the operational oceanographic community [22], includes improved standardized freshwater river inputs (considering not only flow rates but also particulate and dissolved matter key for biogeochemical processes) and foresees, as a longer-term objective, to include connection and coupling with land hydrology models.…”
Section: Introductionmentioning
confidence: 99%